(untitled) (CIPEEX, 2022)
THE PUBLIC TRANSPORT SYSTEM IS KNOWN AS PRECARIOUS, BACKWARD, LACKING IN INVESTMENTS ANDINSPECTIONS. IT IS A VERY IMPORTANT SYSTEM FOR SOCIETY, FOR THE COUNTRY. AMONG THESE AND OTHERNEEDS, WE DESIGNED A TECHNOLOGICAL SYSTEM OF QUALITY AND PRECISION THAT WILL WORK IN FAVOR OFTHE IMPROVEMENT OF THE SYSTEM. THIS PROJECT AIMS TO FACILITATE THE USE OF THE PUBLIC TRANSPORTSYSTEM IN ANÁPOLIS, THROUGH A MOBILE APPLICATION, DEVELOPED FOR ANDROID AND IOS. THEAPPLICATION IS INTENDED TO BE USED BY PUBLIC TRANSPORT USERS, AND AIMS TO PERIODICALLY SEND THECURRENT LOCATION OF THE BUS TO AN EXTERNAL DATABASE, UPDATING INFORMATION ABOUT IT. THE USER WILL FOLLOW THE MOVEMENT OF PUBLIC TRANSPORT ON THE MAP IN REAL TIME, ALLOWING HIM TO SCHEDULE HIS DAY TO DAY MORE EFFICIENTLY, WAITING LESS, AVOIDING ACCIDENTS AND THEFT AND WHERE HE CAN HAVE A BETTER EXPERIENCE WITH TRANSPORT.THE MAIN OBJECTIVE IS THAT THE APPLICATION IS DEVELOPED DURING THE COURSE AND THAT IT ALLOWS USERS TO KNOW: WHAT IS THE CLOSEST POINT, WHAT IS THE ARRIVAL TIME OF EACH BUS. BEING AN APPLICATION AIMED AT PUBLIC TRANSPORT IN ANÁPOLIS AND WILL BE AVAILABLE FOR ANDROID AND IOS SYSTEMS.